The socio-cultural and economic contexts of fertility decline in the rural eastern Terai region of Nepal : a thesis presented in fulfilment of the requirements for the degree of Doctor of Philosophy in Health Management and Policy at Massey University - Karki, Debendra; Karki, Debendra (Massey University, 1998)
There has been a steady decline in fertility in the eastern Terai region of Nepal in the years 1981-1995. The decline in fertility is desirable from the point of view of government, because of the population pressure on the region. Population pressure has been caused, however, not primarily by the high fertility of inhabitants of the region, but more by massive in-migration to the region, indirectly caused by the government policy itself. The government has responded to population pressure in the Terai by seeking to reduce fertility by means of family planning programmes. However, the recent decline in fertility rates in the eastern Terai has little to do with family planning programmes, which were introduced to the region only quite recently. Rather the decline in fertility is primarily the result of a steady rise in the marriage age of women. The rise in age at marriage is the result of economic and social pressures- in particular the difficulty of sustaining a joint family based agrarian livelihood, because of growing population (due to in-migration) and limitation upon further clearing of the forest. A related factor contributing to the rise of marriage age is the quest for urban employment and for the kind of education that would facilitate that employment. Girls are allowed to stay in school longer and boys and girls may travel some distance away from the village for the sake of higher education and job opportunities. While the giving of dowry with a very young daughter in marriage is the prestige model set by the established landed high caste families, the middle caste tribal people and the lower castes practice bride-price payment. Using the micro-demographic research methodology, this dissertation provides a detailed case history of fertility change in a village of a developing country. Fertility rates are shown to be subject to numerous interacting social and economic forces, and changes in fertility can be better understood with the small-scale and precise analytic tools provided by micro-demography. The village of Chisang is composed entirely of recently arrived families. The first immigrants- high caste Hindus from the Hill region- acquired good land and established flourishing farms, but later immigrants were less fortunate. In-migration, through-migration, and out-migration are the defining features of the village history and village demography, and thereby of social structure, family structure, economy, and fertility rates. For all Hindu people in the Terai, the good marriage of each boy and girl, the unquestioned virginity of the girl upon marriage, and the production of offspring within each marriage remain imperative. As the marriage age of women rises, the gap between age at marriage and age of consummation of marriage closes. Though fertility is declining because of the rising age at marriage, villagers say that they have not intentionally planned this chain of cause and effect: for them, it just happened. However, the village is at a stage in its history when the introduction of family planning measures is likely to be, and it appears to have been in the last two years, highly successful.
Keywords: Human fertility; Chisang; Population pressure; Family planning; Marriage age